Participatory visual and digital methods - Gubrium, Aline., author.
1 online resource (227 pages)
Keywords: "Gubrium and Harper describe how visual and digital methodologies can contribute to a participatory, public-engaged ethnography. These methods can change the traditional relationship between academic researchers and the community, building one that is more accessible, inclusive, and visually appealing, and one that encourages community members to reflect and engage in issues in their own communities. The authors describe how to use photovoice, film and video, digital storytelling, GIS, digital archives and exhibits in participatory contexts, and include numerous case studies demonstrating their utility around the world"--